The Imperative of Request in the Sulalatus Salatin and the Archives of Banten Sultanate - Zulfikar Rachman (Bina Nusantara University, 2021)
The research aimed to find the imperative of request in the old manuscripts, analyze its use based on the social status between the speaker and the audience, and analyze the request strategy by analyzing the sentence’s structure. The data were taken from narratives and dialogues of Banten Sultanate archives dated in 1600s to 1800s and the Sulalatus Salatin in 1800s. Therefore, the research design applied a descriptive qualitative method. The use of minta (ask), minta tolong (asking for help), mohon and pohon (beg/pray), and tolong (help) as request markers were described in graphs. The results show that minta is universal, which can be used from a speaker to an audience with lower-higher, equal, and higher-lower statuses. Minta tolong is uttered by a speaker to an audience with lower-higher and equal statuses. In the Sulalatus Salatin, mohon and pohon request markers are the most spoken to a king. Minta is universal, and tolong is uttered by a speaker with higher status to an audience with a lower status. Explanation of the situation, apologies, subject, demand, receiver, verb, reason, hope towards the audience, and attention-getter are components to construct an imperative request in the manuscripts.